Renal Transplant Patients Biopsied for Cause and Tested for C4d, DSA, and IgG Subclasses and C1q: Which Humoral Markers Improve Diagnosis and Outcomes?. (15th January 2017) - Cicciarelli, James C.; Lemp, Nathan A.; Chang, Youngil; Koss, Michael; Hacke, Katrin; Kasahara, Noriyuki; Burns, Kevin M.; Min, David I.; Naraghi, Robert; Shah, Tariq
Abstract : The association between donor specific antibodies (DSA) and renal transplant rejection has been generally established, but there are cases when a DSA is present without rejection. We examined 73 renal transplant recipients biopsied for transplant dysfunction with DSA test results available: 23 patients diffusely positive for C4d (C4d+), 25 patients focally positive for C4d, and 25 patients negative for C4d (C4d−). We performed C1q and IgG subclass testing in our DSA+ and C4d+ patient group. Graft outcomes were determined for the C4d+ group. All 23 C4d+ patients had IgG DSA with an average of 12, 500 MFI (cumulative DSA MFI). The C4d− patients had average DSA less than 500 MFI. Among the patients with C4d+ biopsies, 100% had IgG DSA, 70% had C1q+ DSA, and 83% had complement fixing IgG subclass antibodies. Interestingly, IgG4 was seen in 10 of the 23 recipients' sera, but always along with complement fixing IgG1, and we have previously seen excellent function in patients when IgG4 DSA exists alone. Cumulative DSA above 10, 000 MFI were associated with C4d deposition and complement fixation. There was no significant correlation between graft loss and C1q positivity, and IgG subclass analysis seemed to be a better correlate for complement fixing antibodies in the C4d+ patient group.